Review of Social Accounting and Audit in India: Exploring the Progress and Challenges of Social Accounting in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The creation of the social accounting scheme to monitor personal efficiency is associated with social accounting. In the discourse around enterprise and organisation, sustainability and personal accountability seem to be of growing significance. At the same time, society's worries about how organizations, in terms of social responsibility and sustainability, conduct themselves inspire a need for broader responsibilities. In a comparatively few years, social reporting grew from a very small field of concern and exercise to a vibrant and varied field of studies, education and exercise. By the way, some of this vibration may well be derived from parallel parts of accounting literature on the one side and from financing wider leadership and organizational studies on the other. Throughout this document we address what is, could andor should be social accounting and whether social accounting could have more clearly achieved in increasing and retaining a vigorous discourse. The article offers a short overview to the development of the literature on social accounting. This paper, using descriptive technique, first describes social accounting, its objectives and expectations, then states its present situation and execution of social accounting scheme, indicating personal profitability of accounting data quantity.